Melanocyte progenitor cells reside in human subcutaneous adipose tissue. - Yuri Ikeda (Public Library of Science (PLoS), 2021)
Based on the assumption that some progenitor cells in an organ might reside in neighboring adipose tissue, we investigated whether melanocyte progenitor cells reside in human subcutaneous adipose tissue. First, we examined the expression of human melanoma black 45 (HMB45) and microphthalmia-associated transcription factor (MITF) in undifferentiated adipose-derived stem cells (ADSCs) by immunostaining, RT-PCR, and western blotting. These two markers were detected in undifferentiated ADSCs, and their expression levels were increased in differentiated ADSCs in melanocyte-specific culture medium. Other melanocytic markers (Melan A, MATP, Mel2, Mel EM, tyrosinase, KIT, and PAX3) were also detected at variable levels in undifferentiated ADSCs, and the expression of some markers was increased during differentiation into the melanocyte lineage. We further showed that ADSCs differentiated in melanocyte-specific culture medium localized in the basal layer and expressed tyrosinase and HMB45 in a 3D epidermal culture system. Melanin deposits were also induced by ultraviolet-light-B (UVB) irradiation. These results demonstrate that melanocyte progenitor cells reside in human subcutaneous adipose tissue and that these cells might have the potential to differentiate into mature melanocytes. Melanocyte and keratinocyte progenitors residing in human subcutaneous tissue can be used for the treatment of skin diseases and skin rejuvenation in the future.